Synthesis and Toxicity Test of Schiff Base Compound from 4-Formylpyridine and p¬-Anisidine Using Stirrer Method with Water Solvent - Alfin, Mohammad (Proceedings of the International Conference on Green Technology, 2021)
Abstract- Schiff base is a compound that is produced when primary amine and aldehydes or ketones reacted under certain situations. Schiff base compounds have the characteristic of a C=N (imine) functional group. The Schiff base compound was synthesized from 4-formylpyridine and p -anisidine using a stirrer method with water as the solvent and a 15-minute synthesis time. FTIR spectrophotometer and GC-MS are being used to identify the product of Schiff base compound. The BSLT (Brine Shrimp Lethality Test) method has been used to test the toxicity and LC 50 values are used as parameters for the toxic levels of Schiff base compound. The results showed the synthesis product have a yield 99.86%. The product of the synthesis of Schiff base compounds has a physical characteristics such as: greenish-gray solid with a melting point of 91-93.5 o C. The results of characterization using FTIR showed a typical absorption of the C=N group with the target compound at a wavenumber of 1620 cm -1 . The results of the GC-MS characterization showed one signal with a retention time of 36.5 minutes and a 100% area. The molecular ion of the m/z was 212, which also corresponded to the molecular weight of the compound 4-methoxy-N-(pyridine-4-ylmethylene)aniline. The results of the toxicity test of Schiff's base compound using the BSLT (Bhrine Shrimp Lethality Test) method showed the presence of toxic properties that have potential as anti-cancer with an LC 50 value of 18.66 ppm.